1983
DOI: 10.1128/jcm.18.1.5-9.1983
|View full text |Cite
|
Sign up to set email alerts
|

Serious nosocomial infection caused by Morganella morganii and Proteus mirabilis in a cardiac surgery unit

Abstract: , five patients in the cardiac surgery unit of the Bristol Royal Infirmary developed septicemia caused by Morganella morganii, Proteus mirabilis, or both of these species. Three of the patients had serious wound infections, and three of the patients died. Typing of the M. morganii isolates by 0serotyping and of the P. mirabilis isolates by 0-serotyping, proticine production and sensitivity, and the Dienes reaction confirmed cross infection by both species. Although M. morganii has been regarded as a relatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 20 publications
(24 reference statements)
0
15
0
Order By: Relevance
“…Two of the three cases patients a polymicrobic infection including P. mirabilis. Two of the three cases were fatal (109). Another report described 13 M. morganii infections scattered over four services and five floors of a hospital; this outbreak was eventually resolved when strict aseptic techniques, i.e., hand washing, were reinforced (104).…”
Section: Clinical Significancementioning
confidence: 96%
See 1 more Smart Citation
“…Two of the three cases patients a polymicrobic infection including P. mirabilis. Two of the three cases were fatal (109). Another report described 13 M. morganii infections scattered over four services and five floors of a hospital; this outbreak was eventually resolved when strict aseptic techniques, i.e., hand washing, were reinforced (104).…”
Section: Clinical Significancementioning
confidence: 96%
“…Nosocomial transmission, while uncommon, has been reported. In 1983, Williams et al reported on five patients in a cardiac surgery unit with septicemia caused by either P. mirabilis, Morganella morganii, or both organisms (109). No environmental source was identified, although O serotyping confirmed cross-infection of patients by both species.…”
Section: Clinical Significancementioning
confidence: 99%
“…Such haemolytic strains of M. morganii are highly virulent for mice and cause haemorrhagic lung oedema and death, usually within 4 h of infection (Emody et al, 1982). Furthermore, nosocomial outbreaks of infection with some strains of M. morganii are extensive (Tucci and Isenberg, 1981) and have been associated with serious morbidity and high mortality (Williams et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…naing et al performed corticotropin-releasing hormone tests in 9 patients with MA-induced adrenal suppression. Of those patients, 6 showed an increase in adrenocorticotropin, indicating that suppression was occurring at the hypothalamus in some MA-treated patients (5).…”
Section: Editormentioning
confidence: 99%
“…M. morganii has recently become an important opportunistic pathogen (2)(3)(4)(5)(6), being frequently encountered in the intensive care unit, partly because of its preponderance in immunocompromised individuals and also because of various invasive procedures (7). As first reported by Atalay et al (1), M. morganii caused peritonitis in a polymicrobial fashion (with Providencia rettgeri).…”
mentioning
confidence: 99%